Overexpression of soybean SGF14a enhanced tolerance of transgenic tobacco plants to aluminum stress - Yang Zhili; Guo Chuanlong; Liu Lei; Wu Konghuan; Wang Lin; Li Kunzhi; Zhao Yan; Chen Limei (浙江大学学报. 农业与生命科学版, 2015)
Approximately 30% of the global arable land in the world is acidic soils (pH<5) and China's acidic soil accounts for more than 21% of the area. Aluminum (Al) toxicity is a major limiting factor which limited crop production in acid soils. Al firstly inhibits the growth and development of plant roots. Consequently, it decreased the absorption of water and nutrients, which results in poor growth and production of plants. Therefore, in recent years, many researchers dedicated to study Al tolerance mechanisms and bred high Al-tolerant and acid soil-resistant crops by genetic engineering. 14-3-3 proteins are a group of highly conserved regulatory proteins found in eukaryotic cells, and have roles in regulating plant development and stress responses. A lot of 14-3-3 gene family members are isolated in different plants. 14-3-3 proteins regulate various physiological activities and functions by interacting with phosphorylated or non-phosphorylated target proteins in plants. The expression levels of certain 14-3-3 gene isoforms can be adjusted directly by environmental stimuli.Our previous study showed that Al stress induced the expression of 14-3-3a (SGF14a) in the Al resistant soybean (Glycine max) root tips. In order to further validate the role of SGF14a in response to Al stress in plants, plant expression vectors of SGF14a were constructed. Now, the 35S constitutive promoter was used to overexpress SGF14a. We constructed pK-35S-SGF14a plant expression vectors using gateway technology, then introduced the SGF14a expression vectors into Agrobacterium pMP105, which was transformed into tobacco plants via transformation method. The plants were selected by genomic polymerase chain reaction (PCR), reverse transcriptase-PCR and Western blot analysis. Finally we got three transgenic lines (S11, S19, and S23). The wild type (WT) and transgenic tobacco plants (S11, S19, S23) were treated with 50 μmol/L Al to analyze the effect of SGF14a overexpression on the Al-resistance of tobacco. Changes of the relative root growth, H2O2, malondialdehyde (MDA), soluble protein contents as well as antioxidant enzyme activities in transgenic plants were compared.The results showed that the relative root growth of the transgenic plants increased approximately 1.5-fold as compared with the WT. Moreover, the soluble protein contents in the transgenic tobacco roots increased significantly compared with the WT plants, and antioxidant enzyme activities (peroxidase, catalase, and ascorbate peroxidase) in roots of transgenic tobacco plants also increased when exposed to 50 μmol/L Al. Moreover, the H2O2 accumulation and oxidative stress level in transgenic tobacco roots were reduced under the Al stress. The growth status of the transgenic tobacco was better than that of WT when grown in acidic soil.In summary, the evidences suggest that overexpression of SGF14a an enhance the Al-tolerance of transgenic tobacco and its ability to adapt to acidic soil.